Theories, methods and concepts applied to Ancient History: an interview with Pedro Paulo A. Funari - Funari, Pedro Paulo A. (Romanitas - Revista de Estudos Grecolatinos, 2018)
Interview with Pedro Paulo A. Funari.
Keywords: Interview; Pedro Paulo A. Funari; Ancient History; History's Theory; Methodology